Charting the Path to Peace: Who Bears the Burden of Climate Variability in Indonesia? - Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A systemic analysis of the role that climate, natural resource and food systems play in conflict and peace is key to design and implement interventions addressing and preventing conflict. This document is one part of the 6-policy note outputs from the CGIAR Climate Security Webinar Series. These notes summarize the key messages made during the webinar panel discussion. Recordings of the webinar sessions are available.